1987
DOI: 10.3109/02656738709140373
|View full text |Cite
|
Sign up to set email alerts
|

Development of thermotolerance in CHO cells: Modification by procaine

Abstract: We have tested the reported ability of procaine to inhibit the induction and the development of thermotolerance in Chinese hamster ovary cells. Thermotolerance was induced either by hyperthermia alone (10 min, 45 degrees C) or by combining hyperthermia and procaine (5 min, 45 degrees C + 10 mM procaine) with heating times adjusted to yield similar cell survival after the conditioning treatments. Both the kinetics of thermotolerance development in fresh medium without procaine and the magnitude of thermotoleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, heat-sensitization by procaine has been reported to proceed by other mechanisms as well, such as by alteration of the association of nuclear protein with chromatin after heat shock [Roti Roti and Wilson, 1984]. Several researchers reported that procaine could inhibit the triggering as well as the induction of thermotolerance [Konings, 1985;Rastogi et al, 1987]. Similarly, through inhibition of heat-induced lamin B synthesis, procaine may increase susceptibility to heatinduced cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…However, heat-sensitization by procaine has been reported to proceed by other mechanisms as well, such as by alteration of the association of nuclear protein with chromatin after heat shock [Roti Roti and Wilson, 1984]. Several researchers reported that procaine could inhibit the triggering as well as the induction of thermotolerance [Konings, 1985;Rastogi et al, 1987]. Similarly, through inhibition of heat-induced lamin B synthesis, procaine may increase susceptibility to heatinduced cell killing.…”
Section: Discussionmentioning
confidence: 99%